If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 = -8x + 2(x + -6) Reorder the terms: 30 = -8x + 2(-6 + x) 30 = -8x + (-6 * 2 + x * 2) 30 = -8x + (-12 + 2x) Reorder the terms: 30 = -12 + -8x + 2x Combine like terms: -8x + 2x = -6x 30 = -12 + -6x Solving 30 = -12 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 30 + 6x = -12 + -6x + 6x Combine like terms: -6x + 6x = 0 30 + 6x = -12 + 0 30 + 6x = -12 Add '-30' to each side of the equation. 30 + -30 + 6x = -12 + -30 Combine like terms: 30 + -30 = 0 0 + 6x = -12 + -30 6x = -12 + -30 Combine like terms: -12 + -30 = -42 6x = -42 Divide each side by '6'. x = -7 Simplifying x = -7
| y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a | | -1=6x-31 | | 15.93+.09(x+3)=16.43-.13x | | -3(3y-7)+2(2y+8)= | | 2[-2(4x+5)+4(3x-4)]= | | z/3=11 | | 5x-7=2x-14 | | 7/3.7/5 | | 51=50 | | (x/3)-9= | | -7y-12w=29 | | (-3/7)÷(-14/11) | | -5y-8=-3y+2 | | (4y^2+2y+1)-(y^2-9)= | | 13/11-(-1/7) | | 22x+8=-80 | | -3(4y-9)+2(3y+5)= | | x/x-10=3/1 | | 1/2-(-15/8) | | -24+8a=-5(-3a-4) | | -2.6y+4=.9y-17 | | 2r-8=5r+35 | | 5x+1+x=-27 | | 5t^3-5000=0 | | x+30+45=180 |